Endemism, diversity and priorities for the conservation of serpentine areas in the Barberton Greenstone Belt, Mpumalanga, South Africa - Williamson, Sandra Doris (My University, 2016)
This study aims to provide a comprehensive description of the Flora, biogeography and diversity of the serpentine outcrops of Barberton Greenstone Belt in Mpumalanga, South Africa in order to set conservation priorities for these areas. About 30 large and many smaller serpentine outcrops form part of the Barberton Greenstone Belt and consist of various combinations of serpentinized minerals. Seven outcrops were selected to be studied in detail. A floristic analysis recorded 744 species and subspecies, 319 genera and 94 families. The flora includes 33 taxa endemic to serpentine soils and six taxa, which are hyperaccumulators of nickel. The endemic taxa make up 41 % of the endemics of the Barberton Centre of Endemism. The serpentine flora was found to be different to the surrounding non-serpentine vegetation in terms of numbers of species per family, the ratios of dicotyledons to monocotyledons and familial composition. The Asteraceae and the Anacardiaceae support a higher number of endemics than expected, which suggests genetic pre-adaptation within these families and specifically within the genera Berkheya, Helichrysum and Ozoroa. Most of the endemic taxa exhibit long-range dispersal suggesting gene flow between populations on different outcrops. The endemics represent a mix of neo-endemics and paleoendemics. Non-parametric species richness estimators used to predict the species richness of each site, indicated that five serpentine outcrops have higher species richness than the surrounding non-serpentine areas. Indices of diversity calculated showed similar patterns to those of the species richness estimates. The Barberton Greenstone Belt serpentine outcrops show relatively high plant diversity when compared to some other serpentine outcrops around the world. Beta diversity calculated for each site was not correlated with altitude and weakly correlated with the size of outcrops. Species turnover between outcrops is high and is positively correlated with the geographical distance between outcrops. Diversity at higher taxonomic levels were calculated, and results suggest that genera have some potential for facilitating the ranking of outcrops in terms of biological richness to select sites for conservation planning. Less than 30% of serpentine outcrops are adequately conserved. Species and genus richness and endemism were used to select five outcrops that have high conservation priority
A Thesis submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirement for the degree of Doctor of Philosophy. Johannesburg March 2016
Keywords: Serpentine plants--South Africa--Mpumalanga; Botany--South Africa--Mpumalanga; Greenstone belts--South Africa--Barberton Region